Signal-noise ratio of adaptive geophysical studies - V. I. Roman (Геофизический журнал, 2014)
Spectrum of signal-noise ratio is a conclusive and ultimate factor of adaptive technology of geo-physical and particularly seismic studies and thereafter it is specialized example of universal twofold deterministic-stochastic index of adaptive approximation of physical actuality to their principally unachievable mathematical ideals.